The Effect of Machine Maintenance and Layout on the Production Process - Alifah, Tarisa; Sudarman, Daman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This research aims to analyze the influence of machine maintenance and layout on the production process at PT. Indonesian Packaging Creations. The research method used is a quantitative approach with an associative research design. Data was collected through a questionnaire distributed to 50 respondents who were employees at the company. Data analysis was carried out using multiple linear regression to test the hypothesis that had been formulated. The research results show that machine maintenance has a positive, but not significant, influence on the production process, with a regression coefficient of 0.019 and a significance of 0.738. On the other hand, layout is proven to have a significant influence on the production process, with a regression coefficient of 0.883 and a significance value of 0.000. The simultaneous test shows that the two independent variables have a significant effect on the production process, with a calculated F value of 84.82. This research emphasizes the importance of optimal machine maintenance and efficient layout design to improve the smoothness of the production process. This research provides recommendations for management of PT. Kreasi Kemas Indonesia to implement a better maintenance system and redesign the factory layout to support operational efficiency.